Investing in Mutual Funds Before and During the Covid-19 Pandemic: An Analysis using Markov Chain - Danang Setiawan; Hafizh Nur Novriansyah (Jurnal INTECH Teknik Industri Universitas Serang Raya, 2022)
Indonesian people's interest in stocks and mutual funds is still low compared to other investment instruments. This study aims to evaluate the performance of mutual funds in Indonesia before and during the COVID-19 pandemic. Markov chain is used to assess the performance of each type of mutual fund because of its accuracy and suitability for data showing volatility. The results showed that all types of mutual funds experienced an increase with a probability of more than 50% in the long term. Money market mutual funds, both Islamic and conventional, have the highest probability of increasing by more than 90%. The first passage time can indicate how much price volatility is, wherein in this study, stock mutual funds and sharia stock mutual funds have high volatility. Before conducting further technical analysis, the Markov chain can be used to choose the type of mutual fund that is anticipated to increase.